Communication isolation as reported by a group of deaf Texas inmates - Glasner, Aviva Twersky (Western criminology review, 2010)
Most profoundly deaf children are born into hearing families and often are not exposed to accessible (visualgestural) language within the home environment. Much incidental communication and instruction is missed as a result. This is a qualitative study evaluating the impact of communication barriers on ten deaf, incarcerated offenders whose primary mode of communication is sign language. Participants represent a range of ages, communication histories, and language abilities. Through interviews, participants' experiences in the home, at school, and in the prison environment were discussed. Study results indicate that common experiences of profoundly deaf, adult signing offenders are restricted early access to communication beyond routine activities, lack of signing male role models, being overlooked or faking success in school, and a need for continuing awareness and responsiveness to the communication needs of deaf offenders.